Recent developments in fast spectroscopy for plant mineral analysis - van Maarschalkerweerd, Marie; Husted, Søren (Frontiers in Plant Science, 2015)
Ideal fertilizer management to optimize plant productivity and quality is more relevant than ever, as global food demands increase along with the rapidly growing world population. At the same time, sub-optimal or excessive use of fertilizers leads to severe environmental damage in areas of intensive crop production. The approaches of soil and plant mineral analysis are briefly compared and discussed here, and the new techniques using fast spectroscopy that offer cheap, rapid and easy-to-use analysis of plant nutritional status are reviewed. The majority of these methods use vibrational spectroscopy, such as Visual-Near Infrared (Vis-NIR) and to a lesser extent Ultraviolet (UV) and Mid-Infrared (MIR) spectroscopy. Advantages of and problems with application of these techniques are thoroughly discussed. Spectroscopic techniques considered having major potential for plant mineral analysis, such as chlorophyll a fluorescence, X-ray fluorescence (XRF) and Laser-Induced Breakdown Spectroscopy (LIBS) are also described.